VIOLÊNCIA DOMÉSTICA CONTRA A MULHER E DEPENDÊNCIA FINANCEIRA: Uma análise do Programa Aluguel Maria da Penha no Maranhão - SILVA, Luciana Gomes da (2025)
Given the growing number of cases of domestic violence against women in Brazil, it is observed that one of the factors for some women remaining in the abusive cycle is their financial dependence on the aggressor. Thus, considering the socioeconomic situation of these women and the relevance of state policies to promote female emancipation, the Maria da Penha Rent Program in Maranhão was analyzed in order to understand how social programs implemented by the State can contribute to solve the problem. To this end, in addition to adopting a critical perspective with an essentially qualitative approach, a bibliographic and documentary survey on the subject was carried out, observing its historical determinations and contradictions, in order to understand fundamental aspects in the implementation of a specific social program aimed at addressing domestic violence against women. Thus, it was observed that although this program is well evaluated by the state agents that implement it and can meet the immediate needs of victimized women, in the case of the Maria da Penha Rent Program, there are many flaws in its execution, which permeate the formulation and implementation phases, hindering the achievement of favorable results regarding the goals and, mainly, regarding the desired social transformation, demanding its reformulation. In addition, it was verified that there is a need for greater openness to the participation of victimized women in future public debates so that the proposed social programs are formulated in line with their actual demands and are implemented in an appropriate manner to reach all women in the state. Therefore, it became evident that the Public Authorities must not only propose social policies that help to combat domestic violence against women, considering the situation of financial dependence on the aggressor, but also invest in the deconstruction of the patriarchal culture that contributes to the perpetuation of the problem.